Comparative Analysis of the Transcriptome, Proteome, and miRNA Profile of Kupffer Cells and Monocytes - Andrey Elchaninov; Anastasia Lokhonina; Maria Nikitina; Polina Vishnyakova; Andrey Makarov; Irina Arutyunyan; Anastasiya Poltavets; Evgenia Kananykhina; Sergey Kovalchuk; Evgeny Karpulevich; Galina Bolshakova; Gennady Sukhikh; et al. (Biomedicines, 2020)
Macrophage populations in most mammalian organs consist of cells of different origin. Resident macrophages originate from erythromyeloid precursors of the yolk sac wall; maintenance of the numbers of such macrophages in postnatal ontogenesis is practically independent of bone marrow haematopoiesis. The largest populations of the resident macrophages of embryonic origin are found in the central nervous system (microglia) and liver (Kupffer cells). In contrast, skin dermis and mucous membranes become predominantly colonized by bone marrow-derived monocytes that show pronounced functional and phenotypic plasticity. In the present study, we compared Kupffer cells and monocytes using the immunophenotype, gene expression profile, proteome, and pool of microRNA. The observed differences did not consider the resident liver macrophages as purely M2 macrophages or state that monocytes have purely M1 features. Monocytes show signs of high plasticity and sensitivity to pathogen-associated molecular patterns (e.g., high levels of transcription for Tlr 2, 4, 7, and 8). In contrast, the resident liver macrophages were clearly involved in the regulation of specific organ functions (nitrogen metabolism, complement system protein synthesis).